IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEUANGAN BERBASIS WEB SEBAGAI UPAYA OPTIMALISASI PENGELOLAAN DANA ZIS (ZAKAT, INFAK, SEDEKAH) DI LAZISNU KECAMATAN LIMPUNG - Laksamana Rajendra Haidar Azani Fajri; Imam Syafii; Adhitya Purboyo; Ryan Yunus (Jurnal Riset Teknik Komputer, 2025)
Currently, the Nahdlatul Ulama Zakat, Infaq, and Alms Collection Institution (LAZISNU) in Limpung District still records all donation data manually in books. This method slows down the process of preparing financial reports, often resulting in delays. Therefore, this research aims to create a web-based financial information system. It is hoped that this system will simplify and expedite the management of donation data and the creation of accurate financial reports. To create this system, researchers used the R&D (Research and Development) method, which encompasses various stages, from problem identification and design to testing and product revision. The system will be built using the PHP programming language and a MySQL database. Essentially, this new system is expected to address the problem of manual recording, making data management and financial reporting at LAZISNU Limpung faster, easier, and more accurate